THE STRUGGLE OF SULTAN SAIDKHAN AGAINST SEVINCHKHUJAKHAN IN FERGHANA VALLEY (Scientific journal of the Fergana State University, 2024)
There are many historical sources about the historical events that took place in the 16th century in Movarounnahr, Dashti Kipchak, Khorasan, Kashgar and Iran. They contain valuable information about the history of the Shaibani era of the Ferghana Valley that we are studying. Historical sources and scientific literature were used in the study of the topic under investigation in the article. Historical sources were critically approached based on the degree of relevance of their authors to the narrated events and their personal views. The method of comparative analysis was used in the process of logically connecting the information in the sources. Based on the development of historical events and phenomena in interregional relations, scientific hypotheses were expressed